Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits - Robin R. Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Corrigendum to “Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits” [Quat. Sci. Rev. 389 (2026) 110106] - Robin Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Beyond time and cost: exploring the importance of factors in travel mode choices - Mahyar Vahedi Saheli; Patrick A. Singleton; Antje R.H. Graul (Travel Behaviour and Society, 2025)

Diversity and physiology of abundant Rhodoferax species in global wastewater treatment systems - Jette F. Petersen; Laura C. Valk; Maarten D. Verhoeven; Marta A. Nierychlo; Caitlin M. Singleton; Morten K.D. Dueholm; Per H. Nielsen (Systematic and Applied Microbiology, 2025)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Sugar Consumption in Adults and Children: Are There Differences Across Biological Sex or Socioeconomic Status? - C. Fose; L. Jones; I. Mcpherson; A. Singleton (Journal of the Academy of Nutrition and Dietetics, 2023)

Riders’ perceptions towards transit bus electrification: Evidence from Salt Lake City, Utah - Konstantinos Flaris; Konstantina Gkritza; Patrick A. Singleton; Antje R.H. Graul; Ziqi Song (Transportation Research Part D: Transport and Environment, 2023)

Reprint of: Exploring tourists' motivations, constraints, and negotiations regarding outdoor recreation trips during COVID-19 through a focus group study - Prasanna Humagain; Patrick A. Singleton (Journal of Outdoor Recreation and Tourism, 2023)

Frankia diversity in sympatrically occurring red alder (Alnus rubra) and Sitka alder (Alnus viridis) trees in an early successional environment - Emily R. Wolfe; Sebastian Singleton; Nathan U. Stewart; Mehmet A. Balkan; Daniel J. Ballhorn (Trees, 2022)

Conservation agriculture practices have changed habitat use by rodent pests: implications for management of feral house mice - Wendy A. Ruscoe; Peter R. Brown; Steve Henry; Nikki van de Weyer; Freya Robinson; Lyn A. Hinds; Grant R. Singleton (Journal of Pest Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The early Palaeogene transition from thin-skinned to thick-skinned shortening in the Potosí uplift, Sierra Madre Oriental, northeastern Mexico - Stewart A. Williams; J. S. Singleton; M. G. Prior; S. P. Mavor; G. E. Cross; D.F. Stockli (International Geology Review, 2021)

Comparing Rates of Linage Diversification with Rates of Size and Shape Evolution in Catarrhine Crania - Evan A. Simons; Stephen R. Frost; Katerina Harvati; Kieran McNulty; Michelle Singleton (Evolutionary Biology, 2020)

Genetic risk factors in Parkinson’s disease - K. J. Billingsley; S. Bandres-Ciga; S. Saez-Atienzar; A. B. Singleton (Cell and Tissue Research, 2018)

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Lipid composition and thermal properties of the blubber of Gervais’ beaked whale ( Mesoplodon europaeus ) across ontogeny - Emily M. Singleton; William A. McLellan; Heather N. Koopman; Antje Pokorny; Frederick S. Scharf; D. Ann Pabst (Marine Mammal Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Using wavelet tools to analyse seasonal variations from InSAR time-series data: a case study of the Huangtupo landslide - R. Tomás; Z. Li; J. M. Lopez-Sanchez; P. Liu; A. Singleton (Landslides, 2016)

Early harvest of monsoon rice to address seasonal hunger in northwest Bangladesh - Florencia G. Palis; Arelene J. B. Malabayabas; Grant R. Singleton; Mohammed A. Mazid; David E. Johnson (Food Security, 2016)

Hyperfine interactions and electron distribution in FeIIFeI and FeIFeI models for the active site of the [FeFe] hydrogenases: Mössbauer spectroscopy studies of low-spin FeI - Sebastian A. Stoian; Chung-Hung Hsieh; Michael L. Singleton; Andrea F. Casuras; Marcetta Y. Darensbourg; Kelsey McNeely; Kurt Sweely; Codrina V. Popescu (JBIC Journal of Biological Inorganic Chemistry, 2013)

Connectivity Planning to Address Climate Change - TRISTAN A. NUÑEZ; JOSHUA J. LAWLER; BRAD H. MCRAE; D. JOHN PIERCE; MEADE B. KROSBY; DARREN M. KAVANAGH; PETER H. SINGLETON; JOSHUA J. TEWKSBURY (Conservation Biology, 2013)
As the climate changes, human land use may impede species from tracking areas with suitable climates. Maintaining connectivity between areas of different temperatures could allow organisms to move along temperature gradients and allow species to continue to occupy the same temperature space as the climate warms. We used a coarse‐filter approach to identify broad corridors for movement between areas where human influence is low while simultaneously routing the corridors along present‐day spatial gradients of temperature. We modified a cost–distance algorithm to model these corridors and tested the model with data on current land‐use and climate patterns in the Pacific Northwest of the United States. The resulting maps identified a network of patches and corridors across which species may move as climates change. The corridors are likely to be robust to uncertainty in the magnitude and direction of future climate change because they are derived from gradients and land‐use patterns. The assumptions we applied in our model simplified the stability of temperature gradients and species responses to climate change and land use, but the model is flexible enough to be tailored to specific regions by incorporating other climate variables or movement costs. When used at appropriate resolutions, our approach may be of value to local, regional, and continental conservation initiatives seeking to promote species movements in a changing climate. Planificación de Conectividad para Atender el Cambio Climático

Submarine Groundwater Discharge-Derived Nutrient Loads to San Francisco Bay: Implications to Future Ecosystem Changes - Kimberly A. Null; Natasha T. Dimova; Karen L. Knee; Bradley K. Esser; Peter W. Swarzenski; Michael J. Singleton; Mark Stacey; Adina Paytan (Estuaries and Coasts, 2012)

Meta-analysis of the acute effects of nicotine and smoking on human performance - Stephen J. Heishman; Bethea A. Kleykamp; Edward G. Singleton (Psychopharmacology, 2010)

Distinct characteristics of Ag+ and Cd2+ binding to CopZ from Bacillus subtilis - Margaret A. Kihlken; Chloe Singleton; Nick E. Le Brun (JBIC Journal of Biological Inorganic Chemistry, 2008)

Intestinal Parasites of Free-ranging, Semicaptive,and Captive Pongo abelii in Sumatra, Indonesia - Irene F. Mul; Wardy Paembonan; Ian Singleton; Serge A. Wich; Hester G. van Bolhuis (International Journal of Primatology, 2007)

Variability in the characteristics of cut‐off low pressure systems over subtropical southern Africa - A. T. Singleton; C. J. C. Reason (International Journal of Climatology, 2007)
Variability in the characteristics of cut‐off low pressure systems over subtropical southern Africa is examined for the 1973–2002 period. These characteristics include their seasonality, frequency, duration, location and size. It is found that on average 11 cut‐off lows occur over southern Africa south of 20°S per year and are most common in the March‐May season. Potential relationships between the number of cut‐off lows over southern Africa with the El Niño Southern Oscillation (ENSO), the Pacific South America pattern, the wave number 3 pattern and the semi‐annual oscillation (SAO) are discussed. La Niña years appear to be associated with above average annual frequencies of cut‐off lows but the reverse is generally not true for El Niño years. There was a shift in the preferred season for cut‐off lows from March–May to June–August in the 1980s, which coincided with a weakening of the SAO and a shift in zonal wave number 3. This period also showed a change in the preferred location of these systems from southwestern subtropical southern Africa to the northeast of the region. The results suggest that there may be a relationship between cut‐off lows over subtropical southern Africa, the wave number 3 pattern in the Southern Hemisphere and the SAO. Copyright © 2006 Royal Meteorological Society.

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Physiological basis of reduced Al tolerance in ditelosomic lines of Chinese Spring wheat - Lisa A. Papernik; Ananda S. Bethea; Theresa E. Singleton; Jurandir V. Magalhaes; David F. Garvin; Leon V. Kochian (Planta, 2001)

Cloning, expression, and characterization of pyrrolidone carboxyl peptidase from the archaeon Thermococcus litoralis - M. R. Singleton; S. J. C. Taylor; Julian S. Parrat; J. A. Littlechild (Extremophiles, 2000)

Anthropogenic radionuclides in tide-washed pastures bordering the Irish Sea coast of England and Wales - A. L. Sanchez; A. D. Horrill; B. J. Howard; D. Singleton; K. Mondon (Water, Air, & Soil Pollution, 1998)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)

The effect of social organization on reproductive success and gene flow in colonies of wild house mice, Mus musculus - Grant R. Singleton; David A. Hay (Behavioral Ecology and Sociobiology, 1983)